Directions for research on gender imbalance in the IT profession. Issue 1 (2nd January 2019) - Gorbacheva, Elena; Beekhuyzen, Jenine; vom Brocke, Jan; Becker, Jörg
ABSTRACT: There is a significant shortage of expert Information Technology (IT) personnel in Europe and elsewhere and a marked under-representation of women in the field. This paper identifies important gaps in research on gender imbalance in the IT profession and motivates future Information Systems research to address each of them. First among these gaps is the lack of research on the far-reaching consequences of gender imbalance in the IT profession. Second, despite a considerable body of research, there is the lack of coherent explanation for this imbalance. Third, although many intervention programmes have been implemented in this area, gender diversity in practice has not improved significantly. This research field also requires theorisation based on the cumulative research efforts in the field, comparative studies in various contexts, and longitudinal studies. We point to opportunities to investigate each of these issues and recommend directions for future research and actionable research questions.